Penuangan Isu Bipolar Disorder dalam Karya Tari In Between - Annisa Shafa Dhiyaliza; Ni Nyoman Kasih; Anak Agung Ketut Oka Adnyana (Jurnal IGEL : Journal Of Dance, 2025)
This written work discusses the creation of a choreography titled "In Between," inspired by the experiences ofindividuals with bipolar disorder, explored through emotional duality and social interactions. Emerging from the searchfor balance amidst surging emotions, this piece also delves into the relationship between social norms and emotions, aswell as the personal reflection of the choreographer on this phenomenon. The performance is designed as a site-specificwork at the Grand Room of ISI Denpasar, utilizing visual elements such as curtains as symbols of the boundarybetween two opposing norms. Furthermore, the movement concept is based on the exploration of dance inspired byeveryday life, accompanied by playback music. Collaboration with the Mulawali Institute partner facilitated theresearch and creation process, resulting in a piece that offers reflective space and addresses the issues and complexitiesof and awareness of mental health.Keywords: Bipolar Disorder, Mental Health, Emotional Duality, Social Norms.